Riflettere per formare cittadini riflessivi: specificità della formazione dei formatori - Mignosi, Elena (Studi sulla Formazione/Open Journal of Education, 2017)
The article deals with the theme of reflexivity in learning processes, considering reflexivity as a thinking activity about our own actions and about ourselves in relation with our own actions. In particular, it focuses on the training of trainers and educators, analyzing the specificity and the importance of “learning by experience” not only in initial training, but also during the in-Service training and during working practices. In this sense the article also tackles the theme of “situated learning” (specifying the meaning of “context” in an ecological and systemic perspective) and the concept of “community of practices”. Consequently, the working group and its relevant function in the educational institutions are also deepened.